Limitations to the rapid adoption of M-payment services: Understanding the impact of privacy risk on M-Payment services. (February 2018) - Johnson, Vess L.; Kiser, Angelina; Washington, Ronald; Torres, Russell
Abstract: M-payment services offer many advantages over traditional payment services and analysts have predicted their explosive growth for years. However, despite touted advantages, adoption has been slow. Recent announcements of m-payment services by high-profile providers such as Apple, Google, and PayPal, along with increased vendor support, may spark renewed interest. However, it is unclear whether this will be enough to trigger the long anticipated large-scale adoption. We present a study based on diffusion of innovation theory to investigate the impact of factors influencing m-payment service adoption. In addition, we explore the impact of perceived ubiquity, security, and privacy risk. A sample of 270 survey responses were collected using crowdsourcing and analyzed using SmartPLS. Results of the study indicated that ease of use, relative advantage, visibility and perceived security positively influence the individual's intention to use m-payment services. In addition, ubiquity and trialability positively influence the individual's perception of security while concerns over privacy risks negatively influences perceptions of security. We also discovered that over 46% of those responding to the survey identify as being current users of m-payment services which may suggest a renewed interest on the part of the consumer. Highlights: Ease of use, relative advantage, visibility and perceived security impact usage. Ubiquity and trialability positively impacts perceived security. Perceived privacy risk negatively impacts perceived security. Study utilized crowdsourcing using Mechanical Turk. 46.3% of respondents identified themselves as current users of m-payment services.